Analiza błędów z geometrii elementarnej popełnianych przez kandydatów na studia matematyczne w Akademii Pedagogicznej w Krakowie dokonana na podstawie wyników egzaminów wstępnych na kierunek matematyka w latach 2003 i 2004 - Lubaś, Ewa (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2017)
In the article the errors in the solutions of geometry problems made by the candidates for the first year of the mathematical studies at the Pedagogical University of Cracow during the entrance examinations in 2003 and 2004 are analysed. Every geometry problem is provided with the examples of its solutions, and the detailed conclusions are drawn from the analysis. In the final part of the article a general didactic analysis of the errors is carried out as well as some aspects of teaching necessary to improve students’ knowledge of geometry are taken into consideration.